Two decades of song evolution and revolution on a humpback whale migratory corridor - Athena S. Brown; Rochelle Constantine; Nan Hauser; Ellen C. Garland (Animal Behaviour, 2026)

Concentrations of 4-hydroxychlorothalonil in serum from pregnant women and the association with risk of testicular germ cell cancer in their male offspring - Cecilie S. Uldbjerg; Christian Lindh; David M. Kristensen; Youn-Hee Lim; Jørgen H. Petersen; Karina M. Sørensen; Panu Rantakokko; Brent A. Coull; Elvira V. Bräuner; Russ Hauser; Niels E. Skakkebæk; Anders Juul; et al. (Environmental Research, 2026)

Using Industry-Led Design Competitions to Prepare BME Students for Professional Practice - Walt Baxter; Isgard S. Hueck; Bret Hauser; Sajith Anantharaman; Chloe Chung (Biomedical Engineering Education, 2026)

Sulfur, e-waste contaminants and sharks - Eitan S. Newman; Aviad Scheinin; Natascha Wosnick; Leila Soledade Lemos; Eyal Bigal; Peleg Itay; Tatiana Dillenburg Saint'Pierre; Dan Tchernov; Rachel Ann Hauser-Davis; Danny Morick (Environmental Pollution, 2026)

FOXO3 mediated gene expression modulates doxorubicin sensitivity in human cardiomyocytes - J.G. Faber; M. van Herwijnen; D. Hauser; S. Daemen; F. Caiment; T. van den Beucken (Toxicology, 2025)

Interest and Experience in Culinary Medicine Training and Careers Among Current Nutrition Professionals - L. McClure; S. Hauser; L. Schmitt; C. McManus; S. Harris (Journal of the Academy of Nutrition and Dietetics, 2025)

Cystathionine Gamma-Lyase: A Potential Longevity Gene Under Selection? - Gary J. Ren; Frances E. Hauser; Elissa Khodikian; Nathan R. Lovejoy; Cosima S. Porteus (Journal of Molecular Evolution, 2025)

Macrofauna accelerates nutrient cycling through litterfall in cocoa agroforestry systems - O. Oyedele; D.-G. J. M. Hougni; S. Hauser; A. G. T. Schut; L. S. Woittiez; L. Rusinamhodzi; M. O. Ogunlade; K. E. Giller (Nutrient Cycling in Agroecosystems, 2025)
This study aimed to better understand nitrogen (N), phosphorus (P), and potassium (K) cycling through litterfall in smallholder cocoa agroforestry systems and to assess if these nutrient flows can be measured using standard litterbags. Annual litter production, relative mass loss, and nutrient loss rates from cocoa leaf litter were evaluated in three farms in south-western Nigeria with and without macrofauna access. Litterfall was measured fortnightly close to the base of the cocoa tree and at the edge of the tree canopies from January 2020 to December 2021. Leaf litter decomposition rates were determined over 388 days in 2 mm mesh litterbags to exclude macrofauna and in frames open to the soil surface to allow macrofauna access. Concentrations of C, N, P, and K were measured in the remaining litter at 180, 244, 314, and 388 days after incubation. Annual estimates of litterfall (10.62 Mg DM ha −1 ) did not significantly differ between the traps close to and away from the cocoa tree trunk. Nutrient cycling from litter was estimated at approximately 101 kg N, 5 kg P, and 89 kg K ha −1 year −1 . Relative litter decomposition rates ( k ) significantly differed between frames and litterbags. Macrofauna access significantly reduced the C:N ratio in the remaining litter and increased N and P loss from the litter layer by 28 and 69%, respectively. In conclusion, nutrient flows through litterfall are considerable, and N and P transfer rates to soil are likely underestimated in litterbag experiments that exclude macrofauna.

Lionfish on the Plate: Measures to Control the Species Invasion Result in Human Health Risks - Juliana de Souza-Araujo; Julia Vianna de Pinho; Caroline V. Feitosa; Oscar S. Duarte; Marcelo O. Soares; Rachel Ann Hauser-Davis; Tommaso Giarrizzo (Exposure and Health, 2025)

Prenatal exposure to organochlorine pesticides and polychlorinated biphenyls and risk of testicular germ cell cancer later in life - Cecilie S. Uldbjerg; Panu Rantakokko; Youn-Hee Lim; Jørgen H. Petersen; Karina M. Sørensen; Brent A. Coull; Christian Lindh; Russ Hauser; Elvira V. Bräuner; Niels E. Skakkebæk; Lærke Priskorn; Anders Juul (Science of The Total Environment, 2025)

Divergent Population Structure in Five Common Rockfish Species of Puget Sound, WA Suggests the Need for Species‐Specific Management - Anita Wray; Eleni Petrou; Krista M. Nichols; Robert Pacunski; Larry LeClair; Kelly S. Andrews; Dana Haggarty; Lorenz Hauser (Molecular Ecology, 2025)
Quantifying connectivity between endangered or threatened marine populations is critical information for management and conservation, especially where abundance and productivity differ among such populations. Spatial patterns of such connectivity depend not only on extrinsic factors such as oceanography and bathymetry but also on intrinsic species‐specific factors such as life history, demography and the location of glacial refugia. Nevertheless, population structure is often inferred from related or ecologically similar species. For example, the population structure in most rockfish species ( Sebastes spp.) in the Salish Sea and the US West Coast is currently inferred from genetic data of three species that are known to hybridise in Puget Sound. Here, we determined the population structure and connectivity in five Puget Sound Rockfish species (Black [ Sebastes melanops ], Yellowtail [ S. flavidus ], Redstripe [ S. proriger ], Greenstriped [ S. elongatus ], and Puget Sound Rockfish [ S. emphaeus ]) from over 12,000 restriction‐site associated DNA sequencing (RADseq) loci. We found species‐specific patterns of genetic differentiation, attributable to both extrinsic and intrinsic factors. Specifically, Black and Puget Sound rockfishes showed no genetic differentiation; Yellowtail and Greenstriped rockfishes were structured according to known geographic barriers; and Redstripe Rockfish revealed evidence for temporal genetic differentiation, suggesting irregular recruitment influences population structure. Only Yellowtail Rockfish followed the federal DPS boundaries generally assumed for rockfish, further emphasizing the importance of species‐specific management for the effective recovery and management of these rockfish populations and of marine species in general.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evolution of rhodopsin in flatfishes (Pleuronectiformes) is associated with depth and migratory behavior - Esme S. B. Macpherson; Frances E. Hauser; Alexander Van Nynatten; Belinda S. W. Chang; Nathan R. Lovejoy (Journal of Fish Biology, 2024)
Visual signals are involved in many fitness‐related tasks and are therefore essential for survival in many species. Aquatic organisms are ideal systems to study visual evolution, as the high diversity of spectral properties in aquatic environments generates great potential for adaptation to different light conditions. Flatfishes are an economically important group, with over 800 described species distributed globally, including halibut, flounder, sole, and turbot. The diversity of flatfish species and wide array of environments they occupy provides an excellent opportunity to understand how this variation translates to molecular adaptation of vision genes. Using models of molecular evolution, we investigated how the light environments inhabited by different flatfish lineages have shaped evolution in the rhodopsin gene, which is responsible for mediating dim‐light visual transduction. We found strong evidence for positive selection in rhodopsin, and this was correlated with both migratory behavior and several fundamental aspects of habitat, including depth and freshwater/marine evolutionary transitions. We also identified several mutations that likely affect the wavelength of peak absorbance of rhodopsin, and outline how these shifts in absorbance correlate with the response to the light spectrum present in different habitats. This is the first study of rhodopsin evolution in flatfishes that considers their extensive diversity, and our results highlight how ecologically‐driven molecular adaptation has occurred across this group in response to transitions to novel light environments.

Microstructure development in lacustrine, fine-grained sediments traced by in situ and laboratory testing - S. Oberhollenzer; L. Hauser; A. Baldermann; R. Marte; F. Tschuchnigg; H. F. Schweiger; M. Nachtnebel; M. Dietzel (International Journal of Environmental Science and Technology, 2024)
Soil microstructure, often defined as the combination of particle arrangement and bonding, can strongly influence the stiffness and strength of sedimentary deposits. As undisturbed soil sampling is a challenging task in fine-grained soils, seismic in situ testing is becoming increasingly more important to investigate its mechanical behaviour. The aim of this article is to evaluate the influences of sediment depositional age and structure-forming processes on the degree of soil structure development in Alpine deposits. Seismic in situ and laboratory testing comprising X-ray diffraction (XRD), scanning electron microscopy (SEM), pore water chemical analysis and hydrochemical modelling were executed at three Austrian test sites, namely Lokalbahn Salzburg , Rhesi and water reservoir Raggal . Based on the comparison of in situ shear wave velocities ( V S, SDMT ) with bender element results ( V S, BE ), executed on reconstituted soil specimens, it is shown that the Pleisto–Holocene-aged deposits are characterized by a V S, BE / V S ,SDMT ratio of < 1, indicating the presence of microstructure. However, the youngest sediments (< 50 years) exhibit the weakest microstructure ( V S, BE / V S ,SDMT ≈ 1). The increase of soil structure with sediment age is represented by the updated normalized small-strain rigidity index, K * G , which is situated at the proposed transition between structured and unstructured soils ( K * G = 330), ranging between 250 and 350, at all test sites. The development of microstructure can be attributed to the precipitation of calcite (CaCO 3 ) cements in open pores, which strengthens the interparticle bonding between detrital quartz, feldspar, clay minerals and carbonate grains, subsequently reducing the soil`s porosity with increasing sediment age.

Multiple Ecological Axes Drive Molecular Evolution of Cone Opsins in Beloniform Fishes - Katherine D. Chau; Frances E. Hauser; Alexander Van Nynatten; Jacob M. Daane; Matthew P. Harris; Belinda S. W. Chang; Nathan R. Lovejoy (Journal of Molecular Evolution, 2024)

Metal and metalloid maternal transfer in a newborn West Indian manatee (Trichechus manatus) two years after the northeastern oil spill disaster of 2019 in Brazil - Leila S. Lemos; Fernanda L.N. Attademo; Lauro Henrique de Paiva; Alexandra F. Costa; Laura M.A. Reis; Fábia de Oliveira Luna; Rachel Ann Hauser-Davis; Salvatore Siciliano (Marine Pollution Bulletin, 2024)

Aligning theoretical and empirical representations of soil carbon-to-nitrogen stoichiometry with process-based terrestrial biogeochemistry models - Katherine S. Rocci; Cory C. Cleveland; Brooke A. Eastman; Katerina Georgiou; A. Stuart Grandy; Melannie D. Hartman; Emma Hauser; Hannah Holland-Moritz; Emily Kyker-Snowman; Derek Pierson; Peter B. Reich; Else P. Schlerman; et al. (Soil Biology and Biochemistry, 2024)

Phytosiderophore pathway response in barley exposed to iron, zinc or copper starvation - David Aleksza; Andreea Spiridon; Mika Tarkka; Marie-Theres Hauser; Stephan Hann; Tim Causon; Nicolas Kratena; Christian Stanetty; Timothy S. George; Joanne Russell; Eva Oburger (Plant Science, 2024)

Effect of a behaviour change intervention on household food hygiene practices in rural Bangladesh: A cluster-randomised controlled trial - Shafinaz Sobhan; Anna A. Müller-Hauser; Giorgia Gon; Tarique Md. Nurul Huda; Jillian L. Waid; Amanda S. Wendt; Mahbubur Rahman; Sabine Gabrysch (International Journal of Hygiene and Environmental Health, 2024)

Temporal trends in urinary concentrations of phenols, phthalate metabolites and phthalate replacements between 2000 and 2017 in Boston, MA - Victoria S. Jiang; Antonia M. Calafat; Paige L. Williams; Jorge E. Chavarro; Jennifer B. Ford; Irene Souter; Russ Hauser; Lidia Mínguez-Alarcón (Science of The Total Environment, 2023)

Pubertal progression in relation to peripubertal exposure to organochlorine chemicals in a cohort of Russian boys - Bora Plaku; Paige L. Williams; Oleg Sergeyev; Susan A. Korrick; Jane S. Burns; Jemar R. Bather; Russ Hauser; Mary M. Lee (International Journal of Hygiene and Environmental Health, 2023)

Longitudinal association of prepubertal urinary phthalate metabolite concentrations with pubertal progression among a cohort of boys - J.S. Burns; J.R. Bather; O. Sergeyev; M.M. Lee; S.A. Korrick; S. Sokolov; S. Kovalev; H.M. Koch; A.T. Lebedev; L. Mínguez-Alarcón; R. Hauser; P.L. Williams (Environmental Research, 2023)

Hormone receptor activities of complex mixtures of known and suspect chemicals in personal silicone wristband samplers worn in office buildings - Anna S. Young; Nicholas Herkert; Heather M. Stapleton; Brent A. Coull; Russ Hauser; Thomas Zoeller; Peter A. Behnisch; Emiel Felzel; Abraham Brouwer; Joseph G. Allen (Chemosphere, 2023)

Urinary phthalate metabolite concentrations and hot flash outcomes: Longitudinal associations in the Midlife Women's Health Study - Ryan S. Babadi; Paige L. Williams; Zhong Li; Rebecca L. Smith; Rita S. Strakovsky; Russ Hauser; Jodi A. Flaws; Tamarra James-Todd (Environmental Research, 2023)

A field experiment characterizing variable detection rates during plant surveys - Cindy E. Hauser; Katherine M. Giljohann; Michael A. McCarthy; Georgia E. Garrard; Andrew P. Robinson; Nicholas S. G. Williams; Joslin L. Moore (Conservation Biology, 2022)
Surveys aimed at finding threatened and invasive species can be challenging due to individual rarity and low and variable individual detection rates. Detection rate in plant surveys typically varies due to differences among observers, among the individual plants being surveyed (targets), and across background environments. Interactions among these 3 components may occur but are rarely estimated due to limited replication and control during data collection. We conducted an experiment to investigate sources of variation in detection of 2 Pilosella species that are invasive and sparsely distributed in the Alpine National Park, Australia. These species are superficially similar in appearance to other yellow‐flowered plants occurring in this landscape. We controlled the presence and color of flowers on target Pilosella plants and controlled their placement in plots, which were selected for their variation in cover of non‐target yellow flowers and dominant vegetation type. Observers mimicked Pilosella surveys in the plots and reported 1 categorical and 4 quantitative indicators of their survey experience level. We applied survival analysis to detection data to model the influence of both controlled and uncontrolled variables on detection rate. Orange‐ and yellow‐flowering Pilosella in grass‐ and heath‐dominated vegetation were detected at a higher rate than nonflowering Pilosella . However, this detection gain diminished as the cover of other co‐occurring yellow‐flowering species increased. Recent experience with Pilosella surveys improved detection rate. Detection experiments are a direct and accessible means of understanding detection processes and interpreting survey data for threatened and invasive species. Our detection findings have been used for survey planning and can inform progress toward eradication. Interaction of target and background characteristics determined detection rate, which enhanced predictions in the Pilosella eradication program and demonstrated the difficulty of transferring detection findings into untested environments.

Wie Rezeptormutationen Arzneimittelwirkungen beeinflussen können - David Reiner-Link; Alexander S. Hauser (BIOspektrum, 2022)

The relevance of pedigrees in the conservation genomics era - Stephanie J. Galla; Liz Brown; Yvette Couch‐Lewis (Ngāi Tahu: Te Hapū o Ngāti Wheke, Ngāti Waewae); Ilina Cubrinovska; Daryl Eason; Rebecca M. Gooley; Jill A. Hamilton; Julie A. Heath; Samantha S. Hauser; Emily K. Latch; Marjorie D. Matocq; Anne Richardson; et al. (Molecular Ecology, 2022)
Over the past 50 years conservation genetics has developed a substantive toolbox to inform species management. One of the most long‐standing tools available to manage genetics—the pedigree—has been widely used to characterize diversity and maximize evolutionary potential in threatened populations. Now, with the ability to use high throughput sequencing to estimate relatedness, inbreeding, and genome‐wide functional diversity, some have asked whether it is warranted for conservation biologists to continue collecting and collating pedigrees for species management. In this perspective, we argue that pedigrees remain a relevant tool, and when combined with genomic data, create an invaluable resource for conservation genomic management. Genomic data can address pedigree pitfalls (e.g., founder relatedness, missing data, uncertainty), and in return robust pedigrees allow for more nuanced research design, including well‐informed sampling strategies and quantitative analyses (e.g., heritability, linkage) to better inform genomic inquiry. We further contend that building and maintaining pedigrees provides an opportunity to strengthen trusted relationships among conservation researchers, practitioners, Indigenous Peoples, and Local Communities.

Metal and Metalloid Contamination in Green Sea Turtles (Chelonia mydas) Found Stranded in Southeastern Brazil - Daphne de Albuquerque Bruno; Isabel Q. Willmer; Lucia Helena S. de S. Pereira; Rafael C. C. Rocha; Tatiana D. Saint’Pierre; Paula Baldassin; Ana Carolina S. Scarelli; Amanda Dias Tadeu; Fábio V. Correia; Enrico M. Saggioro; Leila S. Lemos; Salvatore Siciliano; et al. (Frontiers in Marine Science, 2021)
Sea turtles tend to accumulate high metal levels in their tissues and are considered excellent pollution bioindicators. Studies concerning metal contamination in hatchlings, however, are non-existent for one of the most abundant species in Brazil, green sea turtles, while several other metal assessments in juvenile muscles are still scarce. In this context, this study aimed to analyze the concentrations of 12 elements in kidney and muscle samples from green sea turtles ( Chelonia mydas ; n = 24) found stranded in Rio de Janeiro, southeastern Brazil. Elemental concentrations were determined by inductively coupled plasma mass spectrometry (ICP-MS). The presence of fibropapillomatosis, an increasingly common disease in sea turtles which has been associated to metal contamination, was also evaluated. Most elements (Mn, Fe, Co, Ni, Cu, Zn, Cd, Hg, and Pb) were significantly higher in liver, while Al and As were significantly higher in muscle tissue, indicating bioaccumulation of the latter two elements. No differences between juvenile male and female green turtles were observed for either liver or kidney concerning the investigated elements. Literature comparisons of studies conducted in other areas throughout the Brazilian coast indicate higher concentrations of Cd, Mn, As, Hg, and Zn in kidneys, of probable anthropogenic origin. Several statistically significant inter-elemental correlations were observed between toxic elements, indicating similar sources for these environmental contaminants. Significant correlations between Hg in muscle and kidney and As in the same organs suggest bioaccumulation of both elements in muscle. Three individuals assessed herein exhibited fibropapillomatosis, and further assessments in this regard and potential correlations to the detected metal concentrations are currently being carried out. In addition, evaluations concerning other toxic compounds, as well as deleterious cellular effects, are also underway, since total metal concentrations do not reflect total elemental bioavailability.

Riparian areas potentially provide crucial corridors through fragmented landscape for black-capped vireo (Vireo atricapilla) source-sink system - Samantha S. Hauser; Paul L. Leberg (Conservation Genetics, 2021)

A Comprehensive Transcriptome Analysis Identifies FXN and BDNF as Novel Targets of miRNAs in Friedreich’s Ataxia Patients - Julia O. Misiorek; Anna M. Schreiber; Martyna O. Urbanek-Trzeciak; Magdalena Jazurek-Ciesiołka; Lauren A. Hauser; David R. Lynch; Jill S. Napierala; Marek Napierala (Molecular Neurobiology, 2020)
Friedreich’s ataxia (FRDA) is a genetic neurodegenerative disease that is caused by guanine-adenine-adenine (GAA) nucleotide repeat expansions in the first intron of the frataxin ( FXN ) gene. Although present in the intron, this mutation leads to a substantial decrease in protein expression. Currently, no effective treatment is available for FRDA, and, in addition to FXN , other targets with therapeutic potential are continuously sought. As miRNAs can regulate the expression of a broad spectrum of genes, are used as biomarkers, and can serve as therapeutic tools, we decided to identify and characterize differentially expressed miRNAs and their targets in FRDA cells compared to unaffected control (CTRL) cells. In this study, we performed an integrated miRNAseq and RNAseq analysis using the same cohort of primary FRDA and CTRL cells. The results of the transcriptome studies were supported by bioinformatic analyses and validated by qRT-PCR. miRNA interactions with target genes were assessed by luciferase assays, qRT-PCR, and immunoblotting. In silico analysis identified the FXN transcript as a target of five miRNAs upregulated in FRDA cells. Further studies confirmed that miRNA-224-5p indeed targets FXN, resulting in decreases in mRNA and protein levels. We also validated the ability of miRNA-10a-5p to bind and regulate the levels of brain-derived neurotrophic factor ( BDNF ), an important modulator of neuronal growth. We observed a significant decrease in the levels of miRNA-10a-5p and increase in the levels of BDNF upon correction of FRDA cells via zinc-finger nuclease (ZFN)-mediated excision of expanded GAA repeats. Our comprehensive transcriptome analyses identified miRNA-224-5p and miRNA-10a-5p as negative regulators of the FXN and BDNF expression, respectively. These results emphasize not only the importance of miRNAs in the pathogenesis of FRDA but also their potential as therapeutic targets for this disease.

Metal-Associated Biomarker Responses in Crabs from a Marine Protected Area in Southeastern Brazil - G. S. Araujo; P. K. Gusso-Choueri; D. I. T. Favaro; R. C. C. Rocha; T. D. Saint’Pierre; R. A. Hauser-Davis; B. Braz; R. E. Santelli; A. S. Freire; W. T. V. Machado; A. C. F. Cruz; D. M. S. Abessa (Archives of Environmental Contamination and Toxicology, 2020)

HIV-1 Tat and opioids act independently to limit antiretroviral brain concentrations and reduce blood–brain barrier integrity - Crystal R. Leibrand; Jason J. Paris; Austin M. Jones; Quamrun N. Masuda; Matthew S. Halquist; Woong-Ki Kim; Pamela E. Knapp; Angela D. M. Kashuba; Kurt F. Hauser; MaryPeace McRae (Journal of NeuroVirology, 2019)

Metal loads and biomarker suite responses in a tropical carnivorous fish indicative of anthropogenic impacts in a Southeastern Brazilian lagoon - R. S. C. Coimbra; M. S. Mascarenhas; V. B. Saraiva; C. R. Santos; R. M. Lopes; R. A. Hauser-Davis; V. P. S. Oliveira; M. M. Molisani; M. G. Almeida; C. E. Rezende; C. E. V. Carvalho; M. M. Oliveira (Environmental Monitoring and Assessment, 2018)

Migratory interchange of humpback whales (Megaptera novaeangliae) among breeding grounds of Oceania and connections to Antarctic feeding areas based on genotype matching - D. Steel; M. Anderson; C. Garrigue; C. Olavarría; S. Caballero; S. Childerhouse; P. Clapham; R. Constantine; S. Dawson; M. Donoghue; L. Flórez-González; N. Gibbs; et al. (Polar Biology, 2018)

Correction to: Cryptosporidium Spp. Contamination in Perna perna Mussels Destined for Human Consumption in Southeastern Rio de Janeiro, Brazil - A. L. Santos; L. T. F. de Oliveira; A. L. A. Souza; R. A. Hauser-Davis; S. G. De Simone (Bulletin of Environmental Contamination and Toxicology, 2018)

Optimal schedule for monitoring a plant incursion when detection and treatment success vary over time - Mathieu Bonneau; Cindy E. Hauser; Nicholas S. G. Williams; Roger D. Cousens (Biological Invasions, 2018)

Cryptosporidium spp. Contamination in Perna perna Mussels Destined for Human Consumption in Southeastern Rio de Janeiro, Brazil - A. L. Santos; L. T. F. de Oliveira; A. L. A. Souza; R. A. Hauser-Davis; S. G. De Simone (Bulletin of Environmental Contamination and Toxicology, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Decadal shifts in autumn migration timing by Pacific Arctic beluga whales are related to delayed annual sea ice formation - Donna D. W. Hauser; Kristin L. Laidre; Kathleen M. Stafford; Harry L. Stern; Robert S. Suydam; Pierre R. Richard (Global Change Biology, 2017)
Migrations are often influenced by seasonal environmental gradients that are increasingly being altered by climate change. The consequences of rapid changes in Arctic sea ice have the potential to affect migrations of a number of marine species whose timing is temporally matched to seasonal sea ice cover. This topic has not been investigated for Pacific Arctic beluga whales ( Delphinapterus leucas ) that follow matrilineally maintained autumn migrations in the waters around Alaska and Russia. For the sympatric Eastern Chukchi Sea (‘Chukchi’) and Eastern Beaufort Sea (‘Beaufort’) beluga populations, we examined changes in autumn migration timing as related to delayed regional sea ice freeze‐up since the 1990s, using two independent data sources (satellite telemetry data and passive acoustics) for both populations. We compared dates of migration between ‘early’ (1993–2002) and ‘late’ (2004–2012) tagging periods. During the late tagging period, Chukchi belugas had significantly delayed migrations (by 2 to >4 weeks, depending on location) from the Beaufort and Chukchi seas. Spatial analyses also revealed that departure from Beaufort Sea foraging regions by Chukchi whales was postponed in the late period. Chukchi beluga autumn migration timing occurred significantly later as regional sea ice freeze‐up timing became later in the Beaufort, Chukchi, and Bering seas. In contrast, Beaufort belugas did not shift migration timing between periods, nor was migration timing related to freeze‐up timing, other than for southward migration at the Bering Strait. Passive acoustic data from 2008 to 2014 provided independent and supplementary support for delayed migration from the Beaufort Sea (4 day yr −1 ) by Chukchi belugas. Here, we report the first phenological study examining beluga whale migrations within the context of their rapidly transforming Pacific Arctic ecosystem, suggesting flexible responses that may enable their persistence yet also complicate predictions of how belugas may fare in the future.

An environmental forensic approach for tropical estuaries based on metal bioaccumulation in tissues of Callinectes danae - Isabella C. A. C. Bordon; Jorge E. S. Sarkis; Nathalia P. Andrade; Marcos A. Hortellani; Deborah I. T. Favaro; Mauricio H. Kakazu; Marycel E. B. Cotrim; Raquel T. Lavradas; Isabel Moreira; Tatiana D. Saint’Pierre; Rachel Ann Hauser-Davis (Ecotoxicology, 2016)

Quantification of Impacts and Ecosystem Services Loss in New Jersey Coastal Wetlands Due to Hurricane Sandy Storm Surge - Samantha Hauser; Marcia S. Meixler; Magdeline Laba (Wetlands, 2015)

Population structure of humpback whales in the western and central South Pacific Ocean as determined by vocal exchange among populations - Ellen C. Garland; Anne W. Goldizen; Matthew S. Lilley; Melinda L. Rekdahl; Claire Garrigue; Rochelle Constantine; Nan Daeschler Hauser; M. Michael Poole; Jooke Robbins; Michael J. Noad (Conservation Biology, 2015)
For cetaceans, population structure is traditionally determined by molecular genetics or photographically identified individuals. Acoustic data, however, has provided information on movement and population structure with less effort and cost than traditional methods in an array of taxa. Male humpback whales (Megaptera novaeangliae) produce a continually evolving vocal sexual display, or song, that is similar among all males in a population. The rapid cultural transmission (the transfer of information or behavior between conspecifics through social learning) of different versions of this display between distinct but interconnected populations in the western and central South Pacific region presents a unique way to investigate population structure based on the movement dynamics of a song (acoustic) display. Using 11 years of data, we investigated an acoustically based population structure for the region by comparing stereotyped song sequences among populations and years. We used the Levenshtein distance technique to group previously defined populations into (vocally based) clusters based on the overall similarity of their song display in space and time. We identified the following distinct vocal clusters: western cluster, 1 population off eastern Australia; central cluster, populations around New Caledonia, Tonga, and American Samoa; and eastern region, either a single cluster or 2 clusters, one around the Cook Islands and the other off French Polynesia. These results are consistent with the hypothesis that each breeding aggregation represents a distinct population (each occupied a single, terminal node) in a metapopulation, similar to the current understanding of population structure based on genetic and photo‐identification studies. However, the central vocal cluster had higher levels of song‐sharing among populations than the other clusters, indicating that levels of vocal connectivity varied within the region. Our results demonstrate the utility and value of using culturally transmitted vocal patterns as a way of defining connectivity to infer population structure. We suggest vocal patterns be incorporated by the International Whaling Commission in conjunction with traditional methods in the assessment of structure.

Hypothesis-independent pathway analysis implicates GABA and Acetyl-CoA metabolism in primary open-angle glaucoma and normal-pressure glaucoma - Jessica N. Cooke Bailey; Brian L. Yaspan; Louis R. Pasquale; Michael A. Hauser; Jae H. Kang; Stephanie J. Loomis; Murray Brilliant; Donald L. Budenz; William G. Christen; John Fingert; Douglas Gaasterland; Terry Gaasterland; et al. (Human Genetics, 2014)

Population-specific home ranges and migration timing of Pacific Arctic beluga whales (Delphinapterus leucas) - Donna D. W. Hauser; Kristin L. Laidre; Robert S. Suydam; Pierre R. Richard (Polar Biology, 2014)

Investigations and design of pyridine-2-carboxylic acid thiazol-2-ylamide analogs as methionine aminopeptidase inhibitors using 3D-QSAR and molecular docking - Potshangbam Angamba Meetei; Alexander S. Hauser; Prathigadapa S. Raju; R. S. Rathore; N. Prakash Prabhu; Vaibhav Vindal (Medicinal Chemistry Research, 2014)

Providing patient education: impact on quantity and quality of family health history collection - Chris A. Beadles; R. Ryanne Wu; Tiffany Himmel; Adam H. Buchanan; Karen P. Powell; Elizabeth Hauser; Vincent C. Henrich; Geoffrey S. Ginsburg; Lori A. Orlando (Familial Cancer, 2014)

Bisphenol A concentrations in maternal breast milk and infant urine - K. Mendonca; R. Hauser; A. M. Calafat; T. E. Arbuckle; S. M. Duty (International Archives of Occupational and Environmental Health, 2014)

Genome-wide association study and meta-analysis of intraocular pressure - A. Bilge Ozel; Sayoko E. Moroi; David M. Reed; Melisa Nika; Caroline M. Schmidt; Sara Akbari; Kathleen Scott; Frank Rozsa; Hemant Pawar; David C. Musch; Paul R. Lichter; Doug Gaasterland; et al. (Human Genetics, 2014)

Secondary contact and changes in coastal habitat availability influence the nonequilibrium population structure of a salmonid ( O ncorhynchus keta ) - E. L. Petrou; L. Hauser; R. S. Waples; J. E. Seeb; W. D. Templin; D. Gomez‐Uchida; L. W. Seeb (Molecular Ecology, 2013)
Numerous empirical studies have reported lack of migration–drift equilibrium in wild populations. Determining the causes of nonequilibrium population structure is challenging because different evolutionary processes acting at a variety of spatiotemporal scales can produce similar patterns. Studies of contemporary populations in northern latitudes suggest that nonequilibrium population structure is probably caused by recent colonization of the region after the last P leistocene ice age ended ~13 000 years ago. The chum salmon's ( O ncorhynchus keta ) range was fragmented by dramatic environmental changes during the P leistocene. We investigated the population structure of chum salmon on the N orth A laska P eninsula ( NAP ) and, using both empirical data and simulations, evaluated the effects of colonization timing and founder population heterogeneity on patterns of genetic differentiation. We screened 161 single nucleotide polymorphisms and found evidence of nonequilibrium population structure when the slope of the isolation‐by‐distance relationship was examined at incremental spatial scales. In addition, simulations suggested that this pattern closely matched models of recent colonization of the NAP by secondary contact. Our results agree with geological and archaeological data indicating that the NAP was a dynamic landscape that may have been more recently colonized than during the last deglaciation because of dramatic changes in coastal hydrology over the last several thousand years.

Emerging technologies for non-invasive quantification of physiological oxygen transport in plants - P. Chaturvedi; M. Taguchi; S. L. Burrs; B. A. Hauser; W. W. A. W. Salim; J. C. Claussen; E. S. McLamore (Planta, 2013)

Polybrominated Diphenyl Ethers (PBDES) and Polychlorinated Biphenyls (PCBS) in Mussels and Two Fish Species from the Estuary of the Guanabara Bay, Southeastern Brazil - S. F. Gonçalves da Silva; I. M. R. A. Brüning; R. C. Montone; S. Taniguchi; M. J. Cascaes; P. S. Dias; R. C. Lavandier; R. A. Hauser-Davis; I. Moreira (Bulletin of Environmental Contamination and Toxicology, 2013)

Black leaf streak disease and plantain fruit characteristics as affected by tree density and biomass management in a tropical agroforestry system - L. Norgrove; S. Hauser (Agroforestry Systems, 2013)

Octopamine and serotonin have opposite effects on antipredator behavior in the orb-weaving spider, Larinioides cornutus - Thomas C. Jones; Tamer S. Akoury; Christopher K. Hauser; Michael F. Neblett; Brent J. Linville; Andrea A. Edge; Nathaniel O. Weber (Journal of Comparative Physiology A, 2011)

Changes in soil properties and nematode population status under planted and natural fallows in land use systems of southern Cameroon - B. Banful; S. Hauser (Agroforestry Systems, 2011)

Polymorphic variants in tenascin-C (TNC) are associated with atherosclerosis and coronary artery disease - Mollie A. Minear; David R. Crosslin; Beth S. Sutton; Jessica J. Connelly; Sarah C. Nelson; Shera Gadson-Watson; Tianyuan Wang; David Seo; Jeffrey M. Vance; Michael H. Sketch; Carol Haynes; Pascal J. Goldschmidt-Clermont; et al. (Human Genetics, 2011)

Effect of planted fallow systems on Zonocerus variegatus (Orthoptera: Pyrgomorphidae) abundance in the humid forest zone of Southern Cameroon - S. Kekeunou; S. Hauser; S. Weise; J. Messi; I. Moglan (Journal of Pest Science, 2010)

Effects of egg size, parental origin and feeding conditions on growth of larval and juvenile cod Gadus morhua - H. Paulsen; O. S. Kjesbu; V. Buehler; R. A. J. Case; C. Clemmesen; G. Carvalho; L. Hauser; W . F. Hutchinson; E. Moksness; H. OTTERå; A. Thorsen; T. SVåSAND (Journal of Fish Biology, 2009)
An experimental study was performed to disentangle parental and environmental effects on the growth of Atlantic cod Gadus morhua larvae and juveniles. Eggs were collected during the spawning season from spawning pairs (families) kept separately in specially designed spawning compartments. Newly hatched larvae were released simultaneously into two mesocosms of 2500 and 4400 m 3 . Larval growth was monitored by sampling over a 10 week period, after which juveniles were transferred to on‐growing tanks, where they were tagged and kept for up to 2 years. Maternal origin was determined by individual microsatellite genotyping of the larvae ( n = 3949, 24 families) and juveniles ( n = 600). The results showed significant positive correlations between egg size and larval size during the whole mesocosm period. Correlations, however, weakened with time and were no longer significant at the first tank‐rearing sampling at an age of 9 months. Significant family‐specific differences in growth were observed. The coefficient of variation ( c.v. ) was calculated in order to examine variation in standard length of larvae during the mesocosm period. Inter‐family c.v. was on average 69% of intra‐family c.v. Differences in zooplankton densities between the two mesocosms were reflected in larval growth, condition factor and c.v. Low food abundance appeared to reduce c.v. and favour growth of larvae that showed relatively slow growth at high food abundance. It is suggested that genetically determined variation in growth potential is maintained by environmental variability.

Genetic effects in the leukotriene biosynthesis pathway and association with atherosclerosis - David R. Crosslin; Svati H. Shah; Sarah C. Nelson; Carol S. Haynes; Jessica J. Connelly; Shera Gadson; Pascal J. Goldschmidt-Clermont; Jeffery M. Vance; Jason Rose; Chris B. Granger; David Seo; Simon G. Gregory; et al. (Human Genetics, 2009)

Editorial - Lorenz Hauser; Robin S. Waples; Gary R. Carvalho (Fish and Fisheries, 2008)

Whole‐genome analysis of the ammonia‐oxidizing bacterium, Nitrosomonas eutropha C91: implications for niche adaptation - Lisa Y. Stein; Daniel J. Arp; Paul M. Berube; Patrick S. G. Chain; Loren Hauser; Mike S. M. Jetten; Martin G. Klotz; Frank W. Larimer; Jeanette M. Norton; Huub J. M. Op den Camp; Maria Shin; Xueming Wei (Environmental Microbiology, 2007)
Summary Analysis of the structure and inventory of the genome of Nitrosomonas eutropha C91 revealed distinctive features that may explain the adaptation of N. eutropha ‐like bacteria to N‐saturated ecosystems. Multiple gene‐shuffling events are apparent, including mobilized and replicated transposition, as well as plasmid or phage integration events into the 2.66 Mbp chromosome and two plasmids (65 and 56 kbp) of N. eutropha C91. A 117 kbp genomic island encodes multiple genes for heavy metal resistance, including clusters for copper and mercury transport, which are absent from the genomes of other ammonia‐oxidizing bacteria (AOB). Whereas the sequences of the two ammonia monooxygenase and three hydroxylamine oxidoreductase gene clusters in N. eutropha C91 are highly similar to those of Nitrosomonas europaea ATCC 19718, a break of synteny in the regions flanking these clusters in each genome is evident. Nitrosomonas eutropha C91 encodes four gene clusters for distinct classes of haem‐copper oxidases, two of which are not found in other aerobic AOB. This diversity of terminal oxidases may explain the adaptation of N. eutropha to environments with variable O 2 concentrations and/or high concentrations of nitrogen oxides. As with N. europaea , the N. eutropha genome lacks genes for urease metabolism, likely disadvantaging nitrosomonads in low‐nitrogen or acidic ecosystems. Taken together, this analysis revealed significant genomic variation between N. eutropha C91 and other AOB, even the closely related N. europaea , and several distinctive properties of the N. eutropha genome that are supportive of niche specialization.

Validation of operational AVHRR subpixel snow retrievals over the European Alps based on ASTER data - N. Foppa; A. Hauser; D. Oesch; S. Wunderle; R. Meister (International Journal of Remote Sensing, 2007)

The temporal development in a hybridizing population of wild and cultivated chicory ( Cichorium intybus L.) - B. S. SØRENSEN; L. P. KIÆR; R. B. JØRGENSEN; T. P. HAUSER (Molecular Ecology, 2007)
Hybridization and its possible impacts is a subject of increased attention in connection with the risk of unintended gene flow from cultivated (including genetically modified) plants to wild relatives. Whether such gene flow by hybridization is likely to take place depends among other things on the persistence of the hybrids in a natural environment over time. To evaluate this, we studied an experimental hybridizing population of wild and cultivated chicories ( Cichorium intybus ) relative to a previous study on the same population 2 years earlier. We compared the genetic composition, morphology and fitness traits of plants from 2004 to the plants in the same plot in 2002. The majority of the plants in 2004 was more morphologically and genetically intermediate than in 2002. This indicates that no selection towards being wild‐like or cultivar‐like was present over the period of 2 years. Furthermore, no distinct fitness differences existed between the plants of 2004, probably due to most of the plants being intermediate. No hybridization barriers appeared to be present between wild and cultivated chicories beyond the F 1 generation, since F 2 hybrids and backcrosses were in abundance; in fact, hybrids of probably fourth or fifth generation were present. In conclusion, all results indicate that no barriers exist to the temporal persistence of chicory hybrids in a natural environment.

Hierarchical population genetic structure in the commercially exploited shrimp Crangon crangon identified by AFLP analysis - D. Weetman; A. Ruggiero; S. Mariani; P. W. Shaw; A. R. Lawler; L. Hauser (Marine Biology, 2007)

Tracking silence: adjusting vocal production to avoid acoustic interference - S. E. Roian Egnor; Jeanette Graham Wickelgren; Marc D. Hauser (Journal of Comparative Physiology A, 2007)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

Design and validation of a partial-genome microarray for transcriptional profiling of the Bradyrhizobium japonicum symbiotic gene region - F. Hauser; A. Lindemann; S. Vuilleumier; A. Patrignani; R. Schlapbach; H.M. Fischer; H. Hennecke (Molecular Genetics and Genomics, 2006)

Soil water regime under rotational fallow and alternating hedgerows on an Ultisol in southern Cameroon - S. Hauser; L. Norgrove; B. Duguma; E. Asaah (Agroforestry Systems, 2005)

Comparative study of soil properties under Chromolaena odorata, Pueraria phaseoloides and Calliandra calothyrsus - L. -S. Koutika; S. Hauser; J.G. Meuteum Kamga; B. Yerima (Plant and Soil, 2005)

Measuring and modelling plant area index in beech stands - T. Holst; S. Hauser; A. Kirchgner; A. Matzarakis; H. Mayer; D. Schindler (International Journal of Biometeorology, 2004)

Variability in condition and growth of Atlantic cod larvae and juveniles reared in mesocosms: environmental and maternal effects - C. Clemmesen; V. Bühler; G. Carvalho; R. Case; G. Evans; L. Hauser; W. F. Hutchinson; O. S. Kjesbu; H. Mempel; E. Moksness; H. Otteraa; H. Paulsen; et al. (Journal of Fish Biology, 2003)
Standard length, dry mass and RNA : DNA ratio measurements of 3876 Atlantic cod Gadus morhua larvae and juveniles from 26 families of recruit (fish during their first year of spawning) and repeat spawners (fish which were in their subsequent spawning season) reared in two mesocosms (2500 and 4400 m 3 ) under semi‐natural conditions were analysed over a period of 10 weeks using microsatellites. Larvae from recruit spawners were significantly longer and heavier at hatch and throughout the 10 weeks. RNA : DNA ratios from recruit spawner offspring were only significantly higher at week 1. The smaller (2500 m 3 ) mesocosm was characterized by low plankton density during the transition from endogenous to exogenous feeding followed by a higher density during the metamorphosis period (weeks 4 and 5), with the reverse pattern evident in the 4400 m 3 mesocosm. Patterns of larval growth followed patterns of zooplankton density. Significant differences in RNA : DNA ratios between the mesocosms at all comparable sampling dates were found and within each mesocosm individual fish exhibited a wide range of growth and condition responses under the same environmental conditions. RNA : DNA ratios as a function of size differed in the amount of variability between mesocosms, indicating that the higher food density led to a higher proportion of well‐conditioned larvae in the first 3 weeks. Food availability probably has a major role in determining offspring growth and condition, with limited effects due to maternal effects in cases where the broodstock females are approximately of similar size and condition.

Volunteer biomass production between multipurpose tree hedgerows after two years of fallow in southern Cameroon - S. Hauser (Agroforestry Systems, 2002)

Biological properties and molecular characterization of beet chlorosis virus (BChV) - S. Hauser; M. Stevens; M. Beuve; O. Lemaire (Archives of Virology, 2002)

Pedigree analysis and haplotype sharing within diverse groups of Zea mays L. inbreds - J. Romero-Severson; J. S. C. Smith; J. Ziegle; J. Hauser; L. Joe; G. Hookstra (Theoretical and Applied Genetics, 2001)

Performance of a maize/cassava intercrop in tilled and no-till Senna spectabilis alley cropping on an Ultisol in southern Cameroon - S. Hauser; J. N. Ndi; N. R. Hulugalle (Agroforestry Systems, 2000)

Yields of maize/cassava intercrops grown with hedgerows of three multipurpose trees on an acid Ultisol of Cameroon - S. Hauser; J. N. Ndi; N. R. Hulugalle (Agroforestry Systems, 2000)

CC-chemokine receptor 5 polymorphism and age of onset in familial multiple sclerosis - L. F. Barcellos; A. M. Schito; J. B. Rimmler; E. Vittinghoff; A. Shih; R. Lincoln; S. Callier; M. K. Elkins; D. E. Goodkin; J. L. Haines; M. A. Pericak-Vance; S. L. Hauser; et al. (Immunogenetics, 2000)

Nitrogen and phosphorus uptake by maize as affected by particulate organic matter quality, soil characteristics, and land-use history for soils from the West African moist savanna zone - B. Vanlauwe; K. Aihou; S. Aman; B. K. Tossah; J. Diels; O. Lyasse; S. Hauser; N. Sanginga; R. Merckx (Biology and Fertility of Soils, 2000)

Spatial and temporal gradients of earthworm casting activity in alley cropping systems - S. Hauser*; D. O. Asawalam; B. Vanlauwe (Agroforestry Systems, 1998)

Root distribution ofDactyladenia (Acioa) barteri andSenna (Cassia) Siamea in alley cropping on Ultisol. II. Impact on water regime and consequences for experimental design - S. Hauser; M. P. Gichuru (Agroforestry Systems, 1994)

Root distribution ofDactyladenia (Acioa) barteri andSenna (Cassia) siamea in alley cropping on Ultisol. I. Implication for field experimentation - S. Hauser (Agroforestry Systems, 1993)